Tracking the contamination sources of microbial population and characterizing Listeria monocytogenes in a chicken slaughterhouse by using culture-dependent and -independent methods - Jeong, Jiyeon; Song, Hyokeun; Kim, Woo-Hyun; Chae, Myeongju; Lee, Ji-Youn; Kwon, Yong-Kuk; Cho, Seongbeom (Frontiers in Microbiology, 2023)
Listeria monocytogenes is the etiologic agent of listeriosis, a foodborne disease that poses a threat to public health globally. Chicken meat exhibits heightened susceptibility to L. monocytogenes contamination during butchery. The persistence of this pathogen in the slaughterhouse environment enables recurring contamination of meat products. This study aimed at identifying the sources and transmission routes of L. monocytogenes contamination within an abattoir where it was consistently detected for three consecutive years (2019)(2020)(2021). Furthermore, the environmental factors aiding contamination along chicken processing lines were determined by surveying the microbiome within the facility. Samples collected in 2019 to 2021 were subjected to culture-dependent analysis to assess the prevalence, serotypes, and multi-locus sequence typing (MLST) of L. monocytogenes. Additionally, the specimens collected in 2021 underwent cultureindependent analysis via real-time quantitative polymerase chain reaction (qPCR) and 16S rRNA gene amplicon sequencing to identify the contamination sources and characterize the entire microbial community within the slaughterhouse. L. monocytogenes was isolated only from the clean zone, where the final slaughtering stage occurs. Most strains isolated from the final carcasses showed the same genetic cluster as the isolate in the chilling water and were assigned to MLST profile ST3. Culture-independent qPCR confirmed L. monocytogenes contamination in all samples, excluding post-scalding carcasses, prewashed post-evisceration carcasses, and the bleeding areas. Consequently, qPCR enabled more comprehensive identification of L. monocytogenes contamination points than culture-dependent approaches. Moreover, 16S rRNA gene amplicon sequencing demonstrated that psychro-tolerant and spoilage-related bacteria with L. monocytogenes-like attributes exhibited enhanced viability in the clean zone and immersionchilling water. Metagenomics-based source tracking analysis further revealed that the shackles and chilling waters represent predominant sources of cross-contamination between different slaughterhouse zones, whereas the grading and packaging workstations and chilling water in the This is a provisional file, not the final typeset article clean zone were deemed crucial sources affecting final carcass contamination. Collectively, these findings demonstrate through culture-dependent and -independent methods that L. monocytogenes spreads along the slaughter line, contaminating the slaughterhouse. Moreover, by investigating changes in microbial community and bacterial flow along the slaughter line within the facility, the sources influencing carcass contamination can be effectively traced.